Pengembangan Model ADDIE dalam Media Pembelajaran PAI Berbasis Komputer di SMP YAPITA Surabaya - Muhammad Candra Syahputra (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2020)
In the process of learning Islamic education subjects teachers use very conventional lecture methods, teachers should also begin to adapt to the development of special times in the development of information and communication technology that can also be utilized in the educational process, such as the use of computer media in the learning process of Islamic education. chosen because it can use visual media, audio, and also audio visual which is very suitable to be applied in Islamic education in which there are a lot of materials by applying examples, if using a computer then the example can be used with a computer through presentations, the internet, as well the video. Then, the ADDIE model of learning design is one of the system-oriented learning designs, namely designs that produce learning systems that complement all learning components, this model can also be applied in Islamic education learning.